Помогите упростить выражение: 1.(с+4)(с-3)-(с^2+5c)

2/(x+4)x-(x-3)(x+7)

3.a(2a-1)+(a+3)(a-5)

4.(p+3c)c-(3c+p)(c-p)

5.xy(x+y)-(x^2+y^2)(2x-y)

2

Ответы и объяснения

2012-02-01T18:05:32+04:00

1. c^2+c-12-c^2-5c=-5c+12

2. x^2+4x-x^2-4x+21= 21

3.2a^2-a+a^2-2a-15=3a^2-3a-15

4.pc+3c^2-3c^2-pc+3cp+p^2=p^2+3pc

5.yx^2+xy^2-2x^3-2xy^2+yx^2-y^3=2yx^2-xy^2+2x^3+y^3 

Лучший Ответ!
2012-02-01T18:14:41+04:00

1) (с+4)(с-3)-(с^2+5c)= c^2-3c+4c-12-c^2+5c=6c-12 

2) (x+4)x-(x-3)(x+7)= x^2+4x-(x^2+7x-3x-21)=x^2+4x-x^2-7x+3x+21=21

3) a(2a-1)+(a+3)(a-5)=2a^2-a-a^2+5a-3a+15=a^2+a+15

4) (p+3c)c-(3c+p)(c-p)= cp+3c^2-(3c^2-3cp+pc-p^2)= cp+3c^2-3c^2+3cp-pc+p^2=p^2+3cp

5) xy(x+y)-(x^2+y^2)(2x-y)=yx^2+xy^2-2x^3-2xy^2+yx^2-y^3=2yx^2-xy^2+2x^3+y^3

Не забудь выбрать мое решение лучшим!